THE EFFECT OF STAD TYPE COOPERATIVE LEARNING MODELS AND EARNING ABILITY ON LEARNING ACHIEVEMENT NATURAL SCIENCES (Experimental Study at SDIT IQRA` 1 Bengkulu City) - Efri Deplin; Riyanto Riyanto (UNIB Press, 2018)
The purpose of this study was to determine the effect of the STAD type cooperative learning model and the initial ability of the learning outcomes of science in elementary schools. The research method used was the type of STAD at Elementary School IQRA` 1 City of Bengkulu. Data collection techniques using sample techniques and written tests. Data analysis techniques using SPSS 16. Data analysis techniques using SPSS 16. Based on the results of the results obtained there is no significant difference in learning achievement between science learning using the STAD type learning model and the use of Microsoft Power Point with the STAD type learning model without the use of Microsoft Power Point, there is a significant difference in learning achievement between students with high initial abilities and those with low initial ability in science learning who use the STAD type learning model with the use of Microsoft Power Point and the STAD type learning model without the use of Microsoft Power Point, and there is no significant interaction between the use of the learning model (the learning model in this study is the STAD type learning model with the use of Microsoft Power Point and the STAD type learning model without the use of Microsoft Power Point) and the initial level of learning ability on student achievement